Organizational culture and motivation as factors affecting lecturers' performance - Setiawan S, Boyke; Limakrisna, Nandan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this research is to know and analyze: (1) Organizational Culture; (2) Work Motivation; (3) Lecturer Performance; and (4) The Influence of Organizational Culture and Work Motivation on the Performance of Management Study Program Lecturers at the University of Persada Indonesia, YAI, both simultaneously and partially. The research method used in this study was a descriptive survey and an explanatory survey. The unit of analysis in this study was a lecturer at the University of Persada Indonesia YAI's Management Study Program with a sample of 41 people. This type of research is causality, and the time span in this study is cross-sectional.Based on the results of the study it was found that the Organizational Culture at the University of Persada Indonesia, YAI, in fact, some lecturers gave quite good responses; Persada Indonesia University Lecturer Work Motivation YES in general it can be said that it is not good; The performance of lecturers at Persada Indonesia University, YES, is currently not good. Organizational Culture and Work Motivation simultaneously affect Lecturer Performance.Because Organizational Culture is more dominant in influencing Lecturer Performance, being the first priority in improving Lecturer Performance, Universitas Persada Indonesia YA is expected to be able to improve Organizational Culture, so that they are able to work more professionally